Penentuan Alternatif Alat Tangkap Ramah Lingkungan untuk Keberlanjutan Perikanan Tangkap di Kabupaten Kubu Raya - Atmajaya, Onesimus Dhyas Dwi; Rosyadi, Rosyadi; Hisyam, Muhammad (Nekton, 2021)
Kubu Raya Waters has a lot of fishery resources and especially is giant prawns. A fisheries utilization in Kubu Raya Regency using by fishing gears that using in common waters or open waters. However, a problem of capture fisheries faced there is using destructive fishing gears like trawls. Trawls used by fishermen are threats to sustainable fishery resources and environments. Solutions for solving the problem of sustainable fishery resources in Kubu Raya Regency is determination eco-friendly fishing gear. The purpose of this research is to determine an alternative of most eco-friendly fishing gears that are recommended for fisheries activity in Kubu Raya like gillnet, trammel net, handling, and fishing trap. A method from this research using a score standardized function with many factors are; technology, social policy, economic, and environments. The result of this research determined that a gillnet is a recommended fishing gear for all aspects.